Thermal behaviour of blind-bolted connections to hollow and concrete-filled steel tubular columns - Pascual, Ana M.; Romero, Manuel; Tizani, Walid (Elsevier, 2015)
This paper reports on the thermal analysis of blind-bolts connected to concrete filled steel tube (CFST) and hollow steel section (HSS) columns. The aim is therefore the investigation of the temperature distribution in the connected sections and the evaluation of the effects due to concrete filling and anchored bolt extension. For this purpose, experimental and numerical work was carried out. The test programme involved twelve small- scale unloaded specimens where the variables were: tube section dimensions, type of blind-bolt, and hollow or concrete filled steel tubes. Results from the experiments revealed the noteworthy effect of concrete on bolt temperature reduction, the insignificant influence of tube section dimensions, and the limited impact of embedded bolt extension. Finite element models (FEM) of connections were developed to simulate the behaviour of tested pieces. Comparison with tests allowed the calibration of thermal material properties and characteristics of heat flux in interactions. Furthermore, assessments of heat transfer problem on the simulation of small-scale pieces extended to the numerical model of the whole endplate connection between an I-beam and a tubular column. Finally, the suitability of simple methods from Eurocode 3 Part 1.2 and other references to obtain the temperature on the connection was evaluated.